2011
DOI: 10.1007/s11739-011-0702-8
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department crowding and risk of preventable medical errors

Abstract: The objective of the study is to determine the association between emergency department (ED) crowding and preventable medical errors (PME). This was a retrospective cohort study of 533 ED patients enrolled in the National ED Safety Study (NEDSS) in four Massachusetts EDs. Individual patients' average exposure to ED crowding during their ED visit was compared with the occurrence of a PME (yes/no) for the three diagnostic categories in NEDSS: acute myocardial infarction, asthma exacerbation, and dislocation requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 33 publications
2
84
0
4
Order By: Relevance
“…The resulting documents developed by stakeholders from within the specialty have become the criterion standard for the industry to describe ED operations and are used widely to compare ED performance rates. [6][7][8][9][10][11][12][13][14] These definitions have also been necessary for descriptions of policies created by regulatory bodies, including the Centers for Medicare and Medicaid Services (CMS) and The Joint Commission (TJC), and some of the metrics have been endorsed as quality measures by the National Quality Forum. On January 1, 2014, TJC developed and implemented hospital-wide flow program LD.04.02.11 EP 6.…”
mentioning
confidence: 99%
“…The resulting documents developed by stakeholders from within the specialty have become the criterion standard for the industry to describe ED operations and are used widely to compare ED performance rates. [6][7][8][9][10][11][12][13][14] These definitions have also been necessary for descriptions of policies created by regulatory bodies, including the Centers for Medicare and Medicaid Services (CMS) and The Joint Commission (TJC), and some of the metrics have been endorsed as quality measures by the National Quality Forum. On January 1, 2014, TJC developed and implemented hospital-wide flow program LD.04.02.11 EP 6.…”
mentioning
confidence: 99%
“…2 It is widely known that ED crowding and boarding, as well as ambulance diversion, have an adverse impact on the quality and safety of care, yet these practices continue to pose major problems to the daily delivery of care and to public health. 3,4 They reflect health care issues that extend well beyond the walls of the ED, including hospital crowding, patients' limited access to outpatient care and lack of timely access to on-call specialists, and high rates of uninsurance.…”
Section: The Evolving Roles Of the Emergency Care Systemmentioning
confidence: 99%
“…5 Several studies have shown that longer boarding time in the ED increases the morbidity and mortality of patients with hip fracture. [6][7][8][9] In some countries, the length of time in the ED is audited and monitored by the government. In the United Kingdom, for example, the National Health Service audits these times when 5% of the visits result in a wait time of more than 4 hours.…”
Section: Introductionmentioning
confidence: 99%